(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Artificial Intelligence (AI) is rapidly transforming anesthesiology and reanimatology, offering powerful tools for enhancing patient safety, improving diagnostic accuracy, and optimizing clinical decision-making. This article provides a comprehensive analysis of current AI applications in anesthesia depth management, automated drug delivery (closed-loop systems), preoperative risk stratification, and early detection of life-threatening conditions in intensive care units. Special attention is given to AI-driven predictive analytics, personalized treatment protocols, and real-time monitoring systems that support rapid clinical interventions. The advantages and limitations of AI—including accuracy, speed, personalization potential, integration barriers, and ethical considerations—are critically evaluated. Future perspectives highlight the development of fully automated anesthesia systems, multimodal AI platforms, and integration with telemedicine. AI is positioned not as a replacement for clinicians but as an essential assistant that enhances safety, efficiency, and patient-centered care.